Biological Functions for Information and Communication Technologies Theory and Inspiration - Sawai, Hidefumi; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2011)
By incorporating biologically-inspired functions into ICT, various types of new-generation information and communication systems can be created. Just some example of areas already benefiting from such design inspiration are network architectures, information processing, molecular communication, and complex network modeling for solving real world-problems. This book provides the theoretical basis for understanding these developments and explains their practical applications. Highlighted inserts appears throughout to help readers to understand the very latest topics in these emerging research fields. The book ends with a more philosophical discussion on how new ICT solutions can be found by looking at analogous systems in biology. This new way of thinking may help researchers and practitioners to apply innovative ideas in developing next-generation technologies.
Prologue -- Reconsidering Information and Communications Technology From Life -- Molecular Communication as a Biological ICT -- Artificial Chemistry and Molecular Networks -- Signal Transduction in Biological Systems and Its Possible Uses in Computation and Communication Systems -- For Deeper Understanding.
Keywords: Engineering; Chemistry; Artificial intelligence; Bioinformatics; Physics; Engineering design; Engineering; Engineering Design; Artificial Intelligence (incl. Robotics).; Complexity; Computational Biology/Bioinformatics.; Theoretical and Computational Chemistry